2023
DOI: 10.3390/healthcare11212894
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Symptoms in Parents Who Experience Child-to-Parent Violence: The Role of Self-Efficacy Beliefs

Aitor Jiménez-Granado,
Liria Fernández-González,
Joana del Hoyo-Bilbao
et al.

Abstract: Previous research suggests that parents involved in child-to-parent violence (CPV) experience shame, judgment, and a lack of social support, often accompanied by feelings of self-blame and helplessness as well as a deterioration in their perception of self-efficacy and their parenting skills. All of these factors may impact parents’ mental health. However, there is a research gap concerning the consequences of CPV among parents. Therefore, the objective of this study was to examine the relationship between CPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Previous studies have shown a significant negative correlation between self-efficacy beliefs and interpersonal sensitivity among parents involved in parent-child violence. 22 Low self-efficacy and low ability to solve interpersonal problems are among the risk factors for the development of depression. 23 The results of a longitudinal data from four years of Chinese college students also show that the level of general self-efficacy plays a very important role in the probability of depression.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a significant negative correlation between self-efficacy beliefs and interpersonal sensitivity among parents involved in parent-child violence. 22 Low self-efficacy and low ability to solve interpersonal problems are among the risk factors for the development of depression. 23 The results of a longitudinal data from four years of Chinese college students also show that the level of general self-efficacy plays a very important role in the probability of depression.…”
Section: Introductionmentioning
confidence: 99%